Answer:
![a(x+3)^3, a \\eq 0](https://img.qammunity.org/2022/formulas/mathematics/college/945cl20zio1wwhs259mty66mr21x1h4kos.png)
Explanation:
Zeros of a function:
Given a polynomial f(x), this polynomial has roots
such that it can be written as:
, in which a is the leading coefficient.
Zero at x= -3 with a multiplicity of 3.
This means that:
![x_1 = x_2 = x_3 = -3](https://img.qammunity.org/2022/formulas/mathematics/college/v1ehw36ou901xcyi92ozoc7un4458g9eox.png)
So
![a(x - (-3))*(x - (-3))*(x-(-3)) = a(x+3)(x+3)(x+3) = a(x+3)^3](https://img.qammunity.org/2022/formulas/mathematics/college/xujdk9wzqvq8fsu27f3e2tjbt1nw3f3zsr.png)
Positive leading coefficient
![a(x+3)^3, a \\eq 0](https://img.qammunity.org/2022/formulas/mathematics/college/945cl20zio1wwhs259mty66mr21x1h4kos.png)